2023
DOI: 10.24246/persi.v6i1.p1-14
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Koneksi Politik terhadap Tingkat Real Earnings Management di Indonesia

Abstract: Penelitian ini bertujuan untuk membuktikan bahwa terdapat pengaruh dari koneksi politik terhadap manajemen laba riil (real earnings management). Beberapa penelitian sebelumnya menemukan bahwa koneksi politik dianggap dapat memberikan pengaruh positif terhadap tingkat manajemen laba, namun beberapa penelitian lain menyatakan hal yang sebaliknya. Koneksi politik pada penelitian ini diukur menggunakan jumlah dewan direksi dan dewan komisaris terkoneksi politik untuk menunjukkan tinggi atau rendahnya pengaruh. Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Recently, [ 21 ] conducted a study on the quality of financial reporting and corporate governance, which revealed diverse findings on the reporting quality. Additionally, [ 29 ] investigated the influence of board members on financial reporting quality and found a positive impact due to ownership concentration in the firm structure. Moreover, [ 30 ] discovered a significant correlation between ownership concentration and reporting quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, [ 21 ] conducted a study on the quality of financial reporting and corporate governance, which revealed diverse findings on the reporting quality. Additionally, [ 29 ] investigated the influence of board members on financial reporting quality and found a positive impact due to ownership concentration in the firm structure. Moreover, [ 30 ] discovered a significant correlation between ownership concentration and reporting quality.…”
Section: Literature Reviewmentioning
confidence: 99%